Analysis of Figurative Language in Album The Car by Arctic Monkeys - Esther Dame Prizkila; Ahmad Khoirul Akhir Tanjung; Munaja Rahma; Muhammad Nadjmuddin; Depi Kurniati; Marsya Fadila Putri; Muhammad Delta Romadhon (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
This research explores the use of figurative language in the album The Car by Arctic Monkeys, focusing on its role in enhancing lyrical depth within the alternative rock genre. The main objectives are to identify the types of figurative language used and determine the most prevalent type in the album’s lyrics. A descriptive qualitative research design was employed, with data collected by active listening and recording of linguistic phenomena, specifically by analyzing lyrics from the Genius website and listening to the album on Spotify. The analysis was guided by Perrine’s (2017) framework, which categorizes figurative language into 12 types: simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, hyperbole, understatement, and irony. The findings reveal 64 instances of figurative language across the album’s 10 songs, with metaphor being the most frequent (22 instances), followed by symbol (14 instances), irony (11 instances), personification (7 instances), hyperbole (4 instances), paradox (3 instances), understatement (1 instance), simile (1 instance), and synecdoche (1 instance). Notably, apostrophe, metonymy, and allegory were absent. The study concludes that figurative language significantly enriches the artistic expression of The Car, making the lyrics more engaging and emotionally resonant. These findings contribute to understanding the creative use of language in alternative rock music. Keywords: figurative language, Arctic Monkeys, song lyrics, The Car, music analysis   DOI: https://doi.org/10.5281/zenodo.17837704